2022
DOI: 10.1155/2022/7436577
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Mitochondrial ROS Produced by Skeletal Muscle Mitochondria Promote the Decisive Signal for UPRmt Activation

Abstract: The mitochondrial unfolded protein response (UPRmt) can repair and remove misfolded or unfolded proteins in mitochondria and enhance mitochondrial protein homeostasis. Reactive oxygen species (ROS) produced by regular exercise is a crucial signal for promoting health, and skeletal muscle mitochondria are the primary source of ROS during exercise. To verify whether UPRmt is related to ROS produced by mitochondria in skeletal muscle during regular exercise, we adapted MitoTEMPO, mitochondrially targeted antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Additionally, studies have found that ATF5 plays a critical role in exercise-induced UPRmt and mitochondrial homeostasis because ATF5-knockout muscle displays an enhanced exercise-induced stress kinase signaling response but a blunted UPRmt and mitophagic gene expression response [112]. More recently, our group found that just 12 days of exercise is sufficient for increasing the expression of c-Jun, HSP60, and CLpP in mouse skeletal muscle, which strongly suggests the activation of the classical UPRmt pathway [113]. These results collectively highlight the effectiveness of exercise in promoting the activation of the UPRmt pathway in skeletal muscle.…”
Section: Exercise and The Uprmtmentioning
confidence: 70%
See 1 more Smart Citation
“…Additionally, studies have found that ATF5 plays a critical role in exercise-induced UPRmt and mitochondrial homeostasis because ATF5-knockout muscle displays an enhanced exercise-induced stress kinase signaling response but a blunted UPRmt and mitophagic gene expression response [112]. More recently, our group found that just 12 days of exercise is sufficient for increasing the expression of c-Jun, HSP60, and CLpP in mouse skeletal muscle, which strongly suggests the activation of the classical UPRmt pathway [113]. These results collectively highlight the effectiveness of exercise in promoting the activation of the UPRmt pathway in skeletal muscle.…”
Section: Exercise and The Uprmtmentioning
confidence: 70%
“…This finding contrasts with antioxidant intervention, which inhibits oxidative stress and induces a low-level redox balance, reducing or abolishing exercise-associated stress and preventing the health-promoting effects of exercise. Our group recently demonstrated that inhibiting mitochondrial ROS generation in mice during exercise using MitoTEMPO, a novel cell-penetrating antioxidant targeting mitochondria, reduces the increases in the c-Jun, HSP60, and CLpP levels in the classical pathway of the UPRmt in skeletal muscle, indicating that exercise-derived ROS stimulate the UPRmt [113]. Additionally, an acute burst of ROS from mitochondria induced by the mitochondrial-targeted photosensitizer KillerRed results in the activation of Parkin-dependent mitophagy [129].…”
Section: Exercise Induces Ros To Regulate the Coordination Mechanism ...mentioning
confidence: 99%
“…The disruption of mitochondrial homeostasis is associated with several pathologies, such as neurodegeneration, cancer, aging, and cardiovascular diseases (Chen et al, 2023; Norat et al, 2020; Quirós et al, 2016; Suomalainen and Battersby, 2018). The UPRmt is an evolutionarily conserved homeostatic pathway engaged upon a wide range of mitochondrial insults, including mitochondrial protein misfolding (Zhao et al, 2002), reduced mitochondrial protein import efficiency (Nargund et al, 2012), dissipation of mitochondrial membrane potential (Donehower et al, 2019), and dysregulated levels of reactive oxygen species (ROS) (Wang et al, 2022b). UPRmt activation triggers a broad and protective transcriptional cascade, through enhancing mitochondrial folding capacity and triggering a mitochondrial recovery program, alleviating neurodegenerative and cardiovascular diseases symptomatology (Smyrnias et al, 2019; Sorrentino et al, 2017), promoting resistance to pathogen infection (Mahmud et al, 2020; Pellegrino et al, 2014), and prolonging lifespan (Munkácsy and Rea, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Key to maintaining or adapting mitochondrial functions, the mitochondrial unfolded protein response (UPRmt) is an evolutionarily conserved mitochondria-to-nucleus signalling cascade, initially described as a transcriptional response to the accumulation of misfolded mitochondrial proteins (Martinus et al, 1996; Zhao et al, 2002). Studies have shown that activation of the UPRmt is primarily regulated by the Activating Transcription Factor 5 (ATF5) (Fiorese et al, 2016; Smyrnias et al, 2019; Wang et al, 2019), and engaged upon a wide range of mitochondrial insults, including abnormal level of mitochondrial reactive oxygen species (ROS) (Wang et al, 2022b), dissipation of mitochondrial membrane potential (Rolland et al, 2019), and reduced mitochondrial protein import efficiency (Nargund et al, 2012). Activated UPRmt serves to restore mitochondrial protein homeostasis and promote cell survival in various biological processes, such as innate immune signalling (Pellegrino et al, 2014) and ageing (Houtkooper et al, 2013), as well as adaptation to pathophysiological conditions, such as neurodegenerative disorders (Sorrentino et al, 2017) and cardiovascular diseases (Smyrnias et al, 2019; Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Daily intake of vitamins C and E almost completely eliminated the changes in the expression of these genes and the increase in insulin sensitivity after exercise [129]. Recently, Wang et al [130] demonstrated that regular exercise could activate UPRmt and increase the content of SOD2. However, the expression of c-JUN, the C/EBP homologous protein, HSP60, CLpP, SIRT3, hightemperature-regulated A2 (also known as OMI), and SOD2 decreased after intervention with mitochondrial-derived ROS (mtROS) with the mitochondria-targeted antioxidant MitoTEMPO.…”
Section: Ros Are Necessary For Exercise-induced Skeletal Muscle Healt...mentioning
confidence: 97%